Generating walkability concept for basuki rahmat corridor: a content analysis - Mandasari, Veronica (Institute for Advanced Science Social, and Sustainable Future, 2023)
Walkable City is a term for a city that has good pedestrian paths by considering 6 aspects such as connectivity, linkage with other modes of transportation, sound land use patterns, safety, quality of pedestrian paths, and the condition/atmosphere of pedestrian paths (Southworth, 2005). This study focuses on the Tunjungan area, specifically the Jalan Basuki Rahmat corridor, as it is crucial for accessibility to the trade and service area of Surabaya City. The objective of this study is to evaluate the environment of the Basuki Rahmat Street corridor and assess the current condition of pedestrian pathways. The research inquiries are as follows: 1. Identifying Basuki Rahmat sidewalk condition; 2. Generating Walkability concept through Content Analysis. Before determining the corridor segment for survey purposes, field observations are carried out as a whole. Based on these observations, 2 significant intersections divide the study area into 3 equal sizes. In addition, the existence of bridges as pedestrian crossing facilities and bus stops as pedestrian transit points is an important consideration. The Narrative process is carried out to formulate the concept of developing a walkable city. Based on the analysis results, appropriate development concepts are divided into 2, namely macro and micro development concepts. This is because the analysis of the previous target measures general and specific/detailed things, so it is necessary to distinguish between overall concepts and specific/complex concepts.